The Potential of Centella asiatica as a Feed Additive: Effects on Feed Intake and Growth Performance in Livestock - Citra Nurma Yunita; Reza Fahlevi; Sari Dewi; Amirah Inas Widiawati; Negrita Rizki Anggraini (AgriMalS, 2026)
Optimal livestock productivity is highly dependent on feed efficiency and the maintained animal health status. The use of Antibiotic Growth Promoters (AGPs) has been strictly limited due to the risk of antimicrobial resistance, making natural alternatives crucial for the modern livestock industry. Centella asiatica, a medicinal plant widely recognized for its bioactive compounds, offers significant potential for application in animal nutrition. This plant is rich in triterpenoids, saponins, and flavonoids, which possess antioxidant, anti-inflammatory, and antimicrobial properties that collectively influence livestock metabolism and performance. This study aims to evaluate the potential and effectiveness of Centella asiatica as a feed additive in enhancing feed intake and growth performance across various livestock species. A systematic review was conducted on scientific publications from 2016 to 2026, accessed through online databases such as Google Scholar, PubMed, and ScienceDirect, focusing on the effects of Centella asiatica supplementation on livestock productivity parameters. The results of this review indicate that the inclusion of Centella asiatica in feed rations can improve feed intake, enhance nutrient utilization, and boost growth performance. Furthermore, its bioactive compounds contribute to improved gut health and immune response, which indirectly support superior growth outcomes. Several studies reported that the inclusion of Centella asiatica at optimal levels results in increased body weight gain and improved feed efficiency. In conclusion, Centella asiatica represents an effective natural approach to enhancing growth performance and feed efficiency, making it a highly relevant application in sustainable and antibiotic-free livestock production systems.